SOCIO-ETHICAL NATURE OF PROFESSIONAL CULTURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article describes the issues of professional and ethical culture and its philosophical essence. Today, the state's attention to the high standards of activity of representatives of law enforcement agencies serves to increase their professionalism. Development of the professional and ethical culture of internal affairs officers in the state administration is one of the criteria for the effectiveness of internal affairs bodies.